Building Biological Relevance Into Integrative Modelling of Macromolecular Assemblies - Molza, Anne-Elisabeth; Westermaier, Yvonne; Moutte, Magali; Ducrot, Pierre; Danilowicz, Claudia; Godoy-Carter, Veronica; Prentiss, Mara; Robert, Charles H.; Baaden, Marc; Prévost , Chantal (Frontiers in Molecular Biosciences, 2022)
Recent advances in structural biophysics and in methods to integrate structural data into three-dimensional models have made it possible to unravel the structures of large macromolecular assemblies that have resisted either experimental or theoretical methods alone. However, structures of either stable or even metastable states of macromolecular assemblies are not always sufficient for understanding their dynamics and biological function. To extract biological information from these data requires knowledge about the mechanical and dynamic properties of both the system components and of the entire assemblies. It requires high-resolution data combined with often sophisticated molecular modelling approaches. We illustrate this idea with two examples. In the first example, we describe the components of the ryanodine receptor, an ion channel that controls ion flux across the cell membrane by transitions between open and closed states. The transition-associated conformational changes are small compared to the receptor’s considerable system size; it is challenging to track these states consistently with available cryo-EM structures. We have devised a complete modelling pipeline that includes analyses for obtaining biologically meaningful information. The second example deals with homologous recombination, in which long filaments of a recombinase protein and DNA catalyze the exchange of homologous DNA strands to reliably repair DNA double-strand breaks. The nucleoprotein-filament reaction intermediates in this process are short-lived and heterogeneous, making their structures particularly elusive. We describe how integrating knowledge of the component structures, experimental and theoretical information on mechanical and dynamical properties of the system and its components, combined with cutting-edge modelling tools, can help overcome the lack of such specific structural information. In both examples, we discuss how such interdisciplinary approaches provide new insights into biological processes.